Dissent voting behavior of central bankers: What do we really know? - Roman Horváth; Marek Rusnák; Kateřina Šmídková; Jan Zápal (Charles University in Prague, Institute of Economic Studies (IES), 2012)
We examine the determinants of the dissent in central bank boards' voting records about monetary policy rates in the Czech Republic, Hungary, Sweden, the U.K. and the U.S. In contrast to previous studies, we consider about 25 different macroeconomic, financial, institutional, psychological or preference-related factors jointly and deal formally with the attendant model uncertainty using Bayesian model averaging. We find that the rate of dissent is between 5% and 20% in these central banks. Our results suggest that most regressors, including those capturing the effect of inflation and output, are not robust determinants of voting dissent. The difference in central bankers' preferences is likely to drive the dissent in the U.S. Fed and the Bank of England. For the Czech and Hungarian central banks, average dissent tends to be larger when policy rates are changed. Some evidence is also found that food price volatility tends to increase the voting dissent in the U.S. Fed and in Riksbank.
Keywords: E52; E58; 330; monetary policy; voting record; dissent